Identification and Characterization of Secondary Wall-Associated NAC Genes and Their Involvement in Hormonal Responses in Tobacco (Nicotiana tabacum) - Xu, Na; Meng, Lin; Song, Lin; Li, Xiaoxu; Du, Shasha; Hu, Fengqin; Lv, Yuanda; Song, Wenjing (Frontiers in Plant Science, 2021)
Secondary wall-associated NAC (SWN) genes are a subgroup of NAC (NAM, ATAF, and CUC) transcription factors (TF) that play a key role in regulating secondary cell wall biosynthesis in plants. However, this gene family has not been systematically characterized, and their potential roles in response to hormones are unknown in Nicotiana tabacum. In this study, a total of 40 SWN genes, of which 12 from Nicotiana tomentosiformis, 13 from Nicotiana sylvestris, and 15 from Nicotiana tabacum, were successfully identified. The 15 SWNs from Nicotiana tabacum were further classified into three groups, namely, vascular-related NAC domain genes (NtVNDs), NAC secondary wall thickening promoting factor genes (NtNSTs), and secondary wall-associated NAC domain genes (NtSNDs). The protein characteristic, gene structure, and chromosomal location of 15 NtSWNs (also named Nt1 to Nt15) were also analyzed. The NtVND and NtNST group genes had five conserved subdomains in their N-terminal regions and a motif (LP[Q/x] L[E/x] S[P/A]) in their diverged C- terminal regions. Some hormones, dark and low-temperature related cis-acting elements, were significantly enriched in the promoters of NtSWN genes. A comprehensive expression profile analysis revealed that Nt4 and Nt12 might play a role in vein development. Others might be important for stem development. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) revealed that in the NtNST group, genes such as Nt7, Nt8, and Nt13 were more sensitive than the genes in NtVND and NtSND groups under abiotic stress conditions. A transactivation assay further suggested that Nt7, Nt8, and Nt13 showed a significant transactivation activity. Overall, SWN genes were finally identified and characterized in diploid and tetraploid tobacco, revealing new insights into their evolution, variation, and homology relationships. Transcriptome, cis-acting element, qRT-PCR, and transactivation assay analysis indicated the roles in hormonal and stress responses, which provided further resources in molecular mechanism and genetic improvement.